Organizational Culture and Competence Effects on Performance with Employee Engagement Moderation - Devi Octavia Leweinzky; Seta A. Wicaksana; Lola Fitria Sari; Nana Nawasiah (Interdisciplinary Social Studies, 2026)
This study analyzes the influence of organizational competence and culture on organizational performance, with employee engagement as a moderating variable. The background emphasizes improving human resources and organizational culture to enhance performance in public institutions, particularly government agencies. Employing a quantitative approach with moderated regression analysis (MRA) via STATA, the study used a saturated sample of 76 respondents. Results show organizational competencies and culture positively and significantly affect employee engagement, which in turn significantly influences organizational performance. However, employee engagement did not significantly moderate the relationship between competencies, organizational culture, and organizational performance. The model explained over 60% of organizational performance variation, indicated by high R-squared values. This study offers novel empirical evidence that employee engagement acts as a mediator, not moderator, in the competence-culture-performance link within Indonesian public sectors—challenging private sector assumptions. Findings urge government agencies to prioritize employee engagement development as a mediating pathway for translating competence and culture investments into performance gains, informing effective human resource strategies for bureaucratic reform.